Study on improvement of impermeability of strongly weathered phyllite by microorganisms - Pengfei Liu; Jing Bi; Fei Gan; Xiaojuan Yang (Case Studies in Construction Materials, 2024)
The technology of strengthening weakness rock based on microbial mineralization has been widely concerned by researchers and engineers in recent years. The uniaxial compressive strength, permeability and microscopic physical properties of strongly weathered phyllite treated by microorganisms were investigated in this study. The microstructure study were conducted using nuclear magnetic resonance (NMR), scanning electron microscope (SEM) and X-ray diffraction (XRD). The results show that effective cementation is generated in weathered phyllite due to the microbial induced carbonate precipitation in the process of microbial modified weathering of phyllite, which can increase the strength up to 39 % of treated phyllite. The NMR results proved that the stone content can significantly affects the pore distribution of improved phyllite samples. The porosity is significantly reduced after adding microorganisms for improvement, the permeability changes from 0.019 to 0.022 md with different treatments in this study. A high stone content can promote the adhesion of microorganisms, which is conducive to the formation of calcium carbonate. Both excessively high or low levels of calcium chloride and urea can significantly affect on microbial and enzyme activities. The XRD results confirm the calcite which generated by the microbe-induced carbonate precipitation. Although the calcite content is low but with a wide distribution range, which can effectively decrease the porosity and permeability. That is to say, the wide distribution of calcite can improve the strength of weathered phyllite.